2018
DOI: 10.1002/ajmg.a.40432
|View full text |Cite
|
Sign up to set email alerts
|

Cleft palate and hypopituitarism in a patient with Noonan‐like syndrome with loose anagen hair‐1

Abstract: Noonan syndrome (NS), the most common of the RASopathies, is a developmental disorder caused by heterozygous germline mutations in genes encoding proteins in the RAS‐MAPK signaling pathway. Noonan‐like syndrome with loose anagen hair (NSLH, including NSLH1, OMIM #607721 and NSLH2, OMIM #617506) is characterized by typical features of NS with additional findings of macrocephaly, loose anagen hair, growth hormone deficiency in some, and a higher incidence of intellectual disability. All NSLH1 reported cases to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Growth retardation, lower BMI and short stature are additional well-known characteristics of Noonan syndrome and display a phenotype-genotype variability of growth patterns in affected individuals [27]. In concordance with this study, we showed that in the general population, common and rare variants in RASA2, SOS2 and MAP2K1 are independently associated with growth characteristics (body mass index, height and growth abnormality) and the association driven by one or more haplotypes in each gene.…”
Section: Discussionsupporting
confidence: 89%
“…Growth retardation, lower BMI and short stature are additional well-known characteristics of Noonan syndrome and display a phenotype-genotype variability of growth patterns in affected individuals [27]. In concordance with this study, we showed that in the general population, common and rare variants in RASA2, SOS2 and MAP2K1 are independently associated with growth characteristics (body mass index, height and growth abnormality) and the association driven by one or more haplotypes in each gene.…”
Section: Discussionsupporting
confidence: 89%
“…This case report showed that quick action to lower sodium level could avoid permanent ODS sequelae. This case report also adds to the rarely described cases of patients with Noonan syndrome and hypopituitarism in the literature (9,10).…”
Section: Discussionsupporting
confidence: 59%
“…Desmopressin has been shown to reduce the rate of serum sodium correction from 0.81 to −0.02 mmol/ L/h, and reduce the magnitude of variation of serum sodium levels (13). While a systematic review showed that while proactive approach with desmopressin was shown to be associated with a lower incidence of overcorrection of serum sodium (14), reactive approach has also been favoured by others (15), and thus, it remains undetermined when desmopressin should optimally be given (9,10). Although the prognosis of ODS is better than previously thought with about half of the patients having favourable outcomes, the same study showed that about 30% of patients admitted to intensive care died at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In GTex[12], numerous variants in PTPN11 , such as rs11066309, rs3741983 and rs11066322 were significantly associated with a decreased expression in atrial appendage, adipose tissue, thyroid and skin and esophagus. Although in consistent with the role of PTPN11 in thyroid function, cancer and autoimmunity[2224], these variants are instead described as eQTLs with TMEM116, ALDH2 and MAPKAPK5-AS1 located up to 500kb upstream of PTPN11 , suggesting that the association observed with rs11066309, rs3741983 and rs11066322 may also be potentially linked to other genes.…”
Section: Discussionmentioning
confidence: 95%